2018
DOI: 10.3390/ijerph15112354
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster Randomized Controlled Trial of a Total Worker Health® Intervention on Commercial Construction Sites

Abstract: This study evaluated the efficacy of an integrated Total Worker Health® program, “All the Right Moves”, designed to target the conditions of work and workers’ health behaviors through an ergonomics program combined with a worksite-based health promotion Health Week intervention. A matched-pair cluster randomized controlled trial was conducted on ten worksites (five intervention (n = 324); five control sites (n = 283)). Worker surveys were collected at all sites pre- and post- exposure at one- and six-months. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 59 publications
1
47
1
Order By: Relevance
“…In our previous worksite-based program for general contractors, "All the Right Moves (ARM)" we found that an intervention focused on both health promotion (through toolbox talks) and health protection (through worksite ergonomic evaluations and changes) was effective in improving worker safety and health behaviors [27]. However, our data suggested that the ARM program could have been more effective if the program included resources and activities specifically targeting the subcontractor.…”
Section: Introductioncontrasting
confidence: 57%
See 3 more Smart Citations
“…In our previous worksite-based program for general contractors, "All the Right Moves (ARM)" we found that an intervention focused on both health promotion (through toolbox talks) and health protection (through worksite ergonomic evaluations and changes) was effective in improving worker safety and health behaviors [27]. However, our data suggested that the ARM program could have been more effective if the program included resources and activities specifically targeting the subcontractor.…”
Section: Introductioncontrasting
confidence: 57%
“…We conducted formative research to determine what characteristics needed to be considered for the success of the intervention and its implementation, and to establish the intervention components and their methods. The focus of the formative research was on the adaptation of a previous and successful worksite-based intervention [27], and determining the feasibility and practical application of the intervention components.…”
Section: Formative Research Conducted To Inform Intervention Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Multifaceted 15 studies reporting on 16 different interventions were identified and grouped within the multifaceted domain [35,49,[62][63][64][65][66][67][68][69][70][71][72][73][74]. 11 interventions from high-quality studies and 2 interventions from medium quality studies presented no benefit of multifaceted workplace-interventions on MSD.…”
Section: Participatory Ergonomicsmentioning
confidence: 99%